2016
DOI: 10.11604/pamj.2016.24.120.8986
|View full text |Cite
|
Sign up to set email alerts
|

Did the call for boycott by the Catholic bishops affect the polio vaccination coverage in Kenya in 2015 ? A cross-sectional study

Abstract: IntroductionPolio eradication is now feasible after removal of Nigeria from the list of endemic countries and global reduction of cases of wild polio virus in 2015 by more than 80%. However, all countries must remain focused to achieve eradication. In August 2015, the Catholic bishops in Kenya called for boycott of a polio vaccination campaign citing safety concerns with the polio vaccine. We conducted a survey to establish if the coverage was affected by the boycott.MethodsA cross sectional survey was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Religious beliefs can have a positive or negative influence on vaccination activities, as previously documented in the literature [44][45][46][47][48]. In our study population, respondents in the various religious groups investigated showed high levels of positive vaccine sentiments, with the exception of the one highlighted earlier.…”
Section: Discussionsupporting
confidence: 72%
“…Religious beliefs can have a positive or negative influence on vaccination activities, as previously documented in the literature [44][45][46][47][48]. In our study population, respondents in the various religious groups investigated showed high levels of positive vaccine sentiments, with the exception of the one highlighted earlier.…”
Section: Discussionsupporting
confidence: 72%
“…Religious beliefs can have a positive or negative influence on vaccination activities as previously documented in literature [44][45][46][47][48]. In our study population, respondents in the various religious groups investigated showed high levels of positive vaccine sentiments, with the exception of the one highlighted earlier.…”
Section: Discussionsupporting
confidence: 63%
“…The measles SIAs implementation guidelines, in line with the Global Measles/Rubella Elimination Plan (2012-2020), emphasizes integrated approaches to achieve and maintain very high levels of population immunity using both routine immunization and SIAs, a significant difference with the initial drives towards Polio that were focused on largely using SIAs. Where religious or ethno-linguistic minorities object to vaccinations, efforts are necessary to quantify vaccination coverage among them and, as needed, take corrective measures [ 20 , 21 ].…”
Section: Sia Implementation Issuesmentioning
confidence: 99%